Communication Strategies Used by Radiologic Technologists to Manage Patient Anxiety and Claustrophobia in MRI Settings A Systematic Review - Zarkan, Abdullah Hatem; Bamunif, Ayah Salem; Hakami, Alanoud Ibrahim; Almehdar, Basmah Mohammed; Names, Dalal Ibrahim Othman; Almotiri, Abeer Khalied; Jafari, Amal Ali; Alazmi, Radiaha Saeed Hameed; Hamzi, Mustafa Ahmed Hamad; Hakami, Majed Ibrahim Ahmed; Tamihi, Ayman Hassan Ali; Halabi, AbdulAziz Hassan Ali (Journal of Ecohumanism, 2026)
Background: Magnetic resonance imaging (MRI) is a critical diagnostic tool, yet the experience frequently triggers significant anxiety and claustrophobia in patients. These psychological barriers can lead to motion artifacts, premature exam termination, and increased healthcare costs. Radiologic Technologists (RTs) are at the frontline of patient interaction, making their communication strategies pivotal in mitigating these distress factors. Objective: This systematic review aims to identify, synthesize, and evaluate the effectiveness of various communication strategies employed by Radiologic Technologists to manage patient anxiety and claustrophobia within the MRI suite. Methods: A systematic search was conducted across major databases (PubMed, CINAHL, Scopus, and Cochrane Library) for peer-reviewed studies published between 2010 and 2024. Studies focusing on RT-led verbal and non-verbal interventions, patient-centered communication, and structured psychological support in MRI settings were included. Quality assessment was performed using the MMAT (Mixed Methods Appraisal Tool). Results: The review identified four primary communication themes—sensory preparation, empathetic engagement, procedural control, and structured coaching—demonstrating that a multi-modal approach combining pre-scan education with real-time verbal support significantly reduces exam "abort rates" and the necessity for pharmacological sedation. Conclusion: Effective communication by Radiologic Technologists is as essential as technical proficiency in ensuring high-quality diagnostic outcomes. While interpersonal skills are highly effective, there is a clear need for standardized communication training protocols within radiologic technology curricula to ensure consistent patient care.